INFLUENCE OF SEXUAL TRANSMITTED INFECTION KNOWLEDGE ON RISKY DATING BEHAVIOR AMONG HIGHSCHOOLERS IN SURABAYA - Idelia Carla Achsan; Nining Febriyana; Dwi Izzati Budiono (UNIVERSITAS AIRLANGGA, 2021)
Background: Adolescence is a period of transition of human bodily, cognitive, and emotional improvement and is a time of formation of sexual mind and experiments. One manner to channel those instincts is by using courting. Awareness of Sexually Transmitted Infections (STI) affects adolescent dating behavior. This study targets to research the correlation between adolescent awareness of STIs with adolescent dating behavior. Methods: This research was observational analytics with a cross-sectional study design. The number of samples was 124 young adults in line with the inclusion criteria which were young men and women in high school for the academic year of 2021/2021, willing to be respondents, and agreed on the informed consent. The sampling method was carried out by purposive sampling. The independent variable in this research was knowledge of sexually transmitted infections, whilst the dependent variable was dating behavior. The collected information has been tested through Fisher Exact Test statistical test at a significant degree of α = 0.05 to decide the level of significance. Results: The outcomes confirmed that almost all respondents, particularly 98 (79%) had proper information of STIs, as many as 26 (21%) had enough information of STIs, and none of the adolescents had terrible knowledge of STIs. As many as 115 (92.7%) have no risky dating behavior and 9 (7.3%) of adolescence have dating behavior at risk of getting STIs. After doing the Fisher Exact test, the value of p = 1.00 (p> 0.05) was obtained, thus there is no correlation between knowledge of STIs and adolescent dating behavior statistically. Conclusion: there is no relationship between knowledge of STIs and risky dating behavior amongst adolescence in Surabaya High Schools